Patrones conductuales de los empleados del Gobierno Autónomo Descentralizado Municipal del cantón Ventanas - Suarez Luna, Jaidy Margoth (2021)
The Autonomous Decentralized Government of the canton Ventanas is an institution whose main objective is to promote the economic, social and environmental progress of all citizens who live in the canton, where they have a direct, timely and equitable participation in the different projects that are executed. Behavioral patterns function as one of the main axes of the efficiency and effectiveness of organizations, the same that are established today as an element of great importance, because they are related to the attitude and way of being of the people who make up the entity, since the organizational behavior depends on it as the key to a successful process to form competitive advantages that contribute to the growth of the organization. However, in the Decentralized Autonomous Government of Ventanas there are some inconveniences that are related to the behavior and way of acting of the workers.